Synthesis and antibiotic activity of oxazolidinone–catechol conjugates against Pseudomonas aeruginosa. Issue 47 (28th October 2015) - Paulen, Aurélie; Gasser, Véronique; Hoegy, Françoise; Perraud, Quentin; Pesset, Bénédicte; Schalk, Isabelle J.; Mislin, Gaëtan L. A.
Abstract : An oxazolidinone antibiotic, conjugated to a catechol moiety, was shown to be at least eight times more active against P. aeruginosa, when compared to the linezolid, used as a reference compound. Abstract : Pseudomonas aeruginosa is a Gram-negative pathogenic bacterium responsible for severe infections in which resistance to most of the approved families of antibiotics is increasing. Oxazolidinone antibiotics are active against many Gram-positive bacteria, but are only weakly active against Gram-negative pathogens. We describe the synthesis of conjugates between a catechol moiety and oxazolidinone antibiotics. These conjugates were significantly more active against P. aeruginosa (218–1024 μM) than linezolid (MIC > 1024 μM), the reference molecule from the oxazolidinone family. Antibiotic activity was slightly higher in medium depleted of iron, suggesting the involvement of a bacterial iron uptake system in this biological activity. The bacterial iron uptake pathway involved in the transport is still to be addressed, but the present data excluded a contribution of the enterobactin transporter PfeA.